Arthur and the cootie-catcher - Krensky, Stephen; Brown, Marc Tolon; Fallon, Jon (Boston : Little Brown and Co., 1999)
At Prunella's half-birthday party, her sister unveils a fortune-telling cootie catcher that seems to be able to predict the future.
400
Accelerated Reader AR
Keywords: Cootie catchers -- Fiction; Fortune telling -- Fiction; Aardvark -- Fiction